2002
DOI: 10.1038/sj.sc.3101328
|View full text |Cite
|
Sign up to set email alerts
|

Repair of spinal cord injuries: where are we, where are we going?

Abstract: Repairing the spinal cord has for a long time been a`holy grail' for neuroscientists. No achievement in neuroscience is more di cult to achieve, and none would have the same impact amongst the medical profession and the public. Yet no patient has yet bene®ted from a regeneration therapy. At last su cient progress has been made in the basic science of axon regeneration that treatments that would partially repair a spinal injury are imminent. A full repair of spinal injury still remains elusive. This review summ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
61
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 52 publications
0
61
0
Order By: Relevance
“…Based on such morphometric data, the existence of pathologic cord conditions such as compression or atrophy can be assessed in individuals by comparing with the normally expected transverse area of the affected segment. 3,15 One study 9 discussed the relationship between quantitative distance and spinal cord regeneration: improvement in motor function at two spinal levels require that the corticospinal and other descending axonal pathways regenerate over two or more spinal segments, or over a distance of 2-3 cm. 9 The normal human spinal cord has been studied morphometrically using CT 16 and MRI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on such morphometric data, the existence of pathologic cord conditions such as compression or atrophy can be assessed in individuals by comparing with the normally expected transverse area of the affected segment. 3,15 One study 9 discussed the relationship between quantitative distance and spinal cord regeneration: improvement in motor function at two spinal levels require that the corticospinal and other descending axonal pathways regenerate over two or more spinal segments, or over a distance of 2-3 cm. 9 The normal human spinal cord has been studied morphometrically using CT 16 and MRI.…”
Section: Discussionmentioning
confidence: 99%
“…3,15 One study 9 discussed the relationship between quantitative distance and spinal cord regeneration: improvement in motor function at two spinal levels require that the corticospinal and other descending axonal pathways regenerate over two or more spinal segments, or over a distance of 2-3 cm. 9 The normal human spinal cord has been studied morphometrically using CT 16 and MRI. 17 Very large variations in spinal cord size between individuals may present a serious problem when interpreting morphometric analyses using absolute values, such as the area and diameter, 3 and some reports have indicated that such variations exist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of particular clinical relevance would be its application in future interventions designed to promote regeneration since it is anticipated that functional recovery may be limited to only one or two segments in the first attempts at spinal cord repair. 22 The question in general of association between thresholds for different sensory modalities has been addressed frequently in the past, more particularly with regard to the different modalities of pain 23,24 than for innocuous sensation, but with no clear consensus of opinion. Of particular interest in the present study was the possibility of association of sensory modalities tested at the level of lesion.…”
Section: Discussionmentioning
confidence: 99%
“…19 'Translating these experimental therapies to human patients is enormously challenging and will involve well integrated groups of basic and clinical scientists working together to cross almost entirely uncharted territory. 20 Consequently, clinical centres dealing with spinal cordinjured patients should become prepared to include such novel approaches in their treatment procedures. This means that they should be able to carefully monitor any regeneration effects by clinical, electrophysiological, imaging and behavioural examinations.…”
Section: Introductionmentioning
confidence: 99%